Examining the impacts of DM filters to PFC isolated Ćuk converter for DCM operation by comparing Si and SiC MOSFET - Erdal Şehirli (Springer Science and Business Media LLC, 2023)
AbstractExamining impacts of differential mode (DM) filter topologies covering pi, LC with damping, LC, LCL filter through isolated Ćuk single phase PFC converter is realized in this paper regarding to power factor, THD and efficiency. Application of PFC isolated Ćuk converter is conducted with 42 kHz switching frequency and 50 W power. Each filter is modeled, designed, and applied experimentally via isolated PFC Ćuk converter. Average model derivation based on state-space, for DCM operation of input side inductor of isolated PFC Ćuk converter that is not introduced in literature is the main contribution of the paper. Second main contribution is to analyze filter types by linear methods for the transfer functions cascading the converter and filter transfer functions, which is not presented for PFC converters. It is also presented that solely LCL filter which is not analyzed for PFC converters in detail in literature, does not give desired results. So, increasing the effectivity of LCL filter, new filter structure LCL with parallel C filter is proposed and modeled in this paper. Thanks to the applications, presented results of LCL with parallel C filter is better than others with 4.9% current THD and ‘1’ power factor. Proposed LCL filter ensures 45% reduction of total inductor value, comparing to LC filter. Besides, LCL with C filter provides better control characteristics with maximum allowable gain for stability as 0.7585 higher than other topologies. Moreover, practical design methodology of filter types avoiding complex mathematical procedure is given in this paper. Applications with each filters provide THD requirements, obtained 4.9% as a best value, lower than IEC61000-3-2 standard. Maximum percentage improvement comparing to the IEC61000-3-2 is 27.5% for third harmonic. Furthermore, SiC and Si Mosfets are employed separately in the converter and compared by using each DM filters regarding to power factor, THD, efficiency through applications. As a result, better efficiency with SiC Mosfet as 83% and better THD with Si Mosfet as 4.9% are conducted.
Keywords: Science; Q; R; Medicine; Article